A rhodamine based fluorescent trivalent sensor (Fe3+, Al3+, Cr3+) with potential applications for live cell imaging and combinational logic circuits and memory devices. (19th July 2017) - Alam, Rabiul; Bhowmick, Rahul; Islam, Abu Saleh Musha; katarkar, Atul; Chaudhuri, Keya; Ali, Mahammad
Abstract : A novel sensor (HL 5 ) recognizes sensitively and selectively trivalent metal ions M 3+ (M = Al, Fe and Cr) with prominent enhancement in emission intensities with logic gate circuits and memory devices with living cell imaging application. Abstract : A sensor (HL 5 ) based on rhodamine 6G–en and 3-(3, 5-dimethyl-pyrazol-1-ylmethyl)-2-hydroxy-5-methyl-benzaldehyde (HL 4 ) has been developed for a highly sensitive and selectiveCHEF based recognition of trivalent metal ions M 3+ (M = Al, Fe and Cr) over mono- and di-valent and other biologically abundant trivalent metal ions with prominent enhancement in absorption and emission intensities. A large enhancement of fluorescence intensities for Fe 3+ (21 fold), Al 3+ (14 fold) and Cr 3+ (10 fold) was observed upon addition of 1.8 equivalents of these metals into the probe in methanol/H2 O (1 : 1, v/v, pH 7.2) with the possibility of naked eye detection. The corresponding K f values were evaluated to be 6.7 × 10 4 M −1 (Fe 3+ ); 8.2 × 10 4 M −1 (Al 3+ ) and 6.0 × 10 4 M −1 (Cr 3+ ). The quantum yields ofHL 5 and [HL 5 –Fe 3+ ] and [HL 5 –Cr 3+ ] and [HL 5 –Al 3+ ] complexes in methanol/H2 O (1 : 1, v/v, pH 7.2) are found to be 0.013, 0.290, 0.120, and 0.158, respectively, using rhodamine-6G as the standard. The LOD for Fe 3+, Al 3+ and Cr 3+ were determined by 3σ methods with values 0.29, 0.34 and 0.31 μM, respectively. An arsenate ion snatches Al from the Al–HL 5 complex and quenches its fluorescence via its ring closed spirolactam form. Advanced level molecular logic devices using the inputs 2 and 4 and memory devices, have been constructed. The low cytotoxicity and large enhancement in fluorescence intensity ofHL 5 upon complexation with M 3+ metal ions make the probe suitable for bio-imaging of M 3+ (M = Al, Fe and Cr) in living cells and native cellular iron pools.